Religious Education, Diversity, and Conflict Resolution: A Case Study of Universitas Pendidikan Indonesia Lab School in Building a Culture of Tolerance and Interreligious Dialogue - Fakhruddin, Agus; Rindu Fajar Islamy, Mohammad; Romli, Usup; Eka Subakti, Ganjar (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
Building a culture of tolerance and interreligious dialogue is one of the important agendas for creating religious harmony in various contexts. This study analyzes the concept of religious education and conflict resolution initiated by Universitas Pendidikan Indonesia Lab School in building a culture of tolerance and interfaith dialogue among Muslim and non-Muslim students. UPI Lab School is an educational institution with diverse students from different religious backgrounds. This research used a qualitative approach and descriptive case study method by collecting data through interviews, observation, and documentation. The data analysis employed the Miles and Huberman procedure framework through three stages: data reduction, data display, and conclusion drawing/verification. The result showed several findings: 1) the internalization of religious moderation is manifested in the school’s curriculum and learning process, 2) the learning model is based on freedom and non-coercion and builds a moderate and dynamic discussion space, 3) the school carries out conflict resolution and inter-religious dialogue by communicating with non-Muslim parents and external parties to avoid misunderstanding, and 4) the strengthening of religious identity is built through open discussion based on freedom of opinion for every student, without any form of coercion and discrimination.